Suicídio de fumicultores familiares: construções de um problema social - Drebes, Laila Mayara (2019)
In this thesis, I analyze the processes of social construction concerning suicide of family tobacco farmers at Vale do Rio Pardo, Rio Grande do Sul, Brazil, especially regarding the interference of family members, community, agro-industry, rural extension, public health, Christian church, regional press and a non-governmental organization concerned with suicide prevention. The theoretical-methodological contribution is based on the structuralist constructivism of the sociologist Pierre Bourdieu, with emphasis on the propositions about how the phenomena is socially constructed through the dialectic between exteriority and interiority, valuing social circumstances of the suicide of family tobacco farmers. The study was conducted through a case study, performed in the city of Vale do Rio Pardo, which was selected due to the socioeconomic relevance of tobacco cultivation and high suicide rates. With qualitative nature, primary and secondary data were collected through bibliographies, documents, interviews and observations. The semi-structured interviews were the most relevant instrumento for data collection. The results revealed the contribution of Sociology to denaturalize the phenomenon of suicide by highlighting the multiple material and symbolic interferences of social circumstances, thus recognizing it not only as a biological problem, but also as a sociological problem. However, due to the dichotomy between rural and urban areas, Rural Sociology lingered to assimilate the phenomenon of suicide through the pluralistic interference means of livelyhood and working conditions in rural areas. The families and communities of tobacco farmers reproduce a habitus based on moral values of the economy and work, which in certain personal and professional adverse conditions, triggers processes of social suffering, proper to suicide, especially among men. In the perspective of representatives of the agro-industry, suicides are associated to individual health problems, regardless possible associations between working conditions, suffering and death. Rural extension workers were encouraged to participate in productive diversification processes in areas used for tobacco cultivation, which contributed to trigger an identity crisis, which motivated social suffering among tobacco farmers, due to the struggle against their main economic activity. Public health agents are the most active in suicide prevention, however, grounded on physiologicalpsychological references, they are not always able to denaturalize occupational risks arising from the use of pesticides and the processes of domination and precariousness of labor relations in tobacco farming. Autorities of Catholic and Lutheran religious understand suicide as si and act in the reception of families and communities of tobacco growers in order to prevent suicide. Members of regional press, a subsidiary of the resources of the agribusiness industry, adopt the journalistic orientation of not reporting cases of suicide, which contributes to conceal such social problem. Volunteers of nongovernmental organization specialized in prevention, using psychological references of solidarity listening, find difficulty on reaching rural areas due to poor telephony infrastructure and the habitus of tobacco farmers, regarding controling emotions. It is concluded that at Vale do Rio Pardo, the problem of suicide is wrapped in a field of disputes of different practices and representations, in which social institutions involved try to preserve their own interests, oftenly to the detriment of family tobacco farmer´s lives.